Meta-Analysis Of Nonaka & Takeuchi’s Knowledge Management Model In The Context Of Lifelong Learning - Tammets, Kairit (Journal of Knowledge Management Practice, 2012)
Recently the application of Nonaka & Takeuchi’s organizational knowledge management SECI model for learning has been studied a lot in different settings in learning contexts. A survey-type of study about SECI model is needed for getting better insight about practical aspects of application of the model, also in teacher training context. Study analyzes with qualitative meta-analysis the state of art of using SECI model from 20 research papers. For data analysis an open-ended coding matrix was developed to delineate each study’s purpose, method, learning settings, outcome and technological aspect. Meta-study revealed that SECI is mainly studied in organizational level in the industries’ settings and individual learning has not been in the focus. As a result the paper discusses the main findings of SECI meta-study in teacher training context and proposes a concept of crossorganizational SECI activities that may support teachers’ lifelong learning and professional development.